Pengaruh Sistem Kerja, Kompensasi Dan Kesejahteraan Terhadap Kinerja Tenaga Outsourcing di Bank BNI Kota Padang - Ika Arista Rosanti; Doni Marlius (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to examine and analyze the effect of work systems, compensation and welfare on the performance of outsourcing workers at Bank BNI, Padang City. This type of research is quantitative research with multiple linear regression data analysis. The sample of this research is outsourced employees who work at BNI Bank in Padang City. Samples were taken using saturated sampling technique. The number of respondents 88 people. Data was collected using a questionnaire. The variables in this study are the independent variables, namely the work system (X₁), compensation (X₂) and welfare (X3) and the dependent variable (Y), namely employee performance. From the calculation of the t test, it can be seen that for the work system (X₁) the large t-count value of t-table is 3.947 > 0.677 and a significant value is 0.00 <0.05. For the compensation variable (X2) the large t-count value of t-table is 3.859 > 0.677 and a significant value is 0.039 <0.05. The welfare variable (X3) has a large t-count value from t-table 3.047 > 0.677 and a significant value of 0.030 <0.05. So it can be stated that there is a positive and significant influence of the independent variables on the dependent variable partially.